“We’re all on the same journey, but [are taking] different paths:” Relational Connection, Critical Consciousness and Visions of Possibility among Female Adult Literacy Learners - Jaye Jones (Adult Education Research Conference, 2016)
Women Reading for Education, Affinity & Development (WREAD) is a literacy-focused reading and discussion group for African American women with self-defined histories of trauma. The following paper focuses on the links between relational connections in the group and the development of a collective critical consciousness.
Keywords: Adult Literacy; Women; Critical Literacy; Trauma; Critical Consciousness